2021
DOI: 10.33192/smj.2021.100
|View full text |Cite
|
Sign up to set email alerts
|

Role of Laparoscopy in Diagnosis and Treatment of Endometriosis Associated with Infertility: A Prospective Analysis

Abstract: Objective: Endometriosis is often considered as an enigma due to its varied clinical presentation and challenges in diagnosis. The objective of this study is to evaluate the role of laparoscopy in diagnosis and treatment of endometriosis associated with infertility.Materials and Methods: Infertile females diagnosed to have endometriosis during or before undergoing laparoscopic surgery from August 2018 to February 2020 were followed up for spontaneous conception for 6 months following laparoscopy. Revised Ameri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Also, endometriosis, similar to pain, has an effect on people's mental states and personalities (21). Previous studies have shown that endometriosis negatively affects a person's self-image and causes loss of physical strength and fertility (17,22,23). Mothers who have daughters are concerned that their daughters may develop endometriosis in the future and suffer from pain and infertility (17).…”
Section: Discussionmentioning
confidence: 99%
“…Also, endometriosis, similar to pain, has an effect on people's mental states and personalities (21). Previous studies have shown that endometriosis negatively affects a person's self-image and causes loss of physical strength and fertility (17,22,23). Mothers who have daughters are concerned that their daughters may develop endometriosis in the future and suffer from pain and infertility (17).…”
Section: Discussionmentioning
confidence: 99%